The purification and tribological property of the synthetic magnesium silicate hydroxide modified by oleic acid. (12th July 2018) - Gao, Kai; Chang, Qiuying; Wang, Bin; Zhou, Ningning; Qing, Tao
Abstract: Modified magnesium silicate hydroxide (MMSH) nanoparticles were synthesised hydrothermally using MgO and SiO2 as precursors and oleic acid as modification agent under alkaline condition. The tribological performances of MMSH as lubricant additives were studied. The X‐ray diffraction and Fourier transform infrared spectroscopy spectra show that the synthetic MMSH nanoparticles contain no Mg (OH)2 impurity and belong to the serpentine group. The tribological tests indicate that both MMSH and magnesium silicate hydroxide (MSH) without modification by oleic acid as additives can improve the antiwear property of base oil significantly. Meanwhile, MMSH presents better antiwear property than MSH which attributes to the formation of a tribofilm containing iron oxides, silicon oxides, graphite, Fe3 C, FeOOH, and also organic compounds.